A Noisy Rational Expectations Equilibrium for Multi-Asset Securities Markets - Admati, Anat R. (Econometrica, 1985)
[This paper finds in closed form a noisy rational expectations equilibrium for a class of economies with many risky assets and analyzes the properties of such equilibria. Because of the various interactions between the assets, phenomena appear that do not arise in models with a single risky asset. For example, an asset's equilibrium price might be decreasing in its own payoff and/or increasing in its own supply; an asset might be a Giffen good; a higher price for an asset (holding other prices fixed) might be "bad news" for the asset's payoff; and even for assets in fixed supply, uncertainty about other assets' supplies may prevent their prices from being fully revealing.]